Iranian policy towards Iraq in light of the geopolitical changes in the Middle East (priorities, bets, and challenges (قضايا سياسية, 2023)
This study examines the strategic stakes taken by Iran's policy towards Iraq and its practices in the context of a regional context that is witnessing rapid geopolitical changes, mixed with an Iranian desire to emphasize its indispensability to all regional equations in the Middle East to ensure its national interests. The study seeks to clarify the strategic effectiveness of Iranian attempts to delineate a new geopolitical reality in the region by developing its relations with Iraq, in addition to being a proactive tool to deter geopolitical influences that target its vital interests. The study also discusses the challenges and threats facing the Iranian strategy in the context of transformations, whether on the Iraqi political arena or at the regional and international levels.